Final height of patients with congenital heart disease - Soon Ju Lee; Young Kuk Cho; Jae Sook Ma (Korean Pediatric Society, 2010)
Purpose : Growth impairment is usually observed in children with congenital heart disease (CHD). Studies on the final height and weight of this population are insufficient. Our aim was to evaluate the final height of children with CHD and to identify the relationship between CHD and growth. Methods : We recorded the values of final height and weights of 105 CHD patients (age, <19 years) who visited Chonnam National University Hospital between November 2000 and March 2009, and we reviewed the medical records. Results : The mean values of weight and height of male CHD patients were significantly lower than those of the normal subjects. Patients with severe growth impairment (below the third percentile of normal) included 5 males (8.6%) and 4 females (8.5%) with height less than normal and 9 males (15.5%) and 8 females (17.0%) with weight less than normal. The mean growth of the patients in the cyanotic heart disease group was lower than that of normal subjects, but a statistically significant difference was noted in the weights of males. In a comparative study based on the type of CHD, a significant difference was noted in weights of males. Patients with patent ductus arteriosus and those with tetralogy of Fallot had the highest and lowest mean values of weight, respectively. Conclusion : Growth impairment was more evident in children with CHD than normal children. Patients should be treated during an optimal time frame. Thus, CHD patients should be treated if follow-up studies indicate growth impairment.